2011
DOI: 10.1186/2042-4280-2-5
|View full text |Cite
|
Sign up to set email alerts
|

Circulating herpes simplex type 1 (HSV-1)-specific CD8+T cells do not access HSV-1 latently infected trigeminal ganglia

Abstract: BackgroundTherapeutic vaccines can be designed to enhance existing T cell memory populations for increased protection against re-infection. In the case of herpes simplex virus type 1, recurrent disease results from reactivation of latent virus in sensory ganglia, which is controlled in part by a ganglia-resident HSV-specific memory CD8+ T cell population. Thus, an important goal of a therapeutic HSV-1 vaccine would be to enhance this population.MethodsHSV-1-infected mice were treated with TAK-779 to block CCR5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 45 publications
0
41
0
2
Order By: Relevance
“…The study demonstrated that both shedding of reactivated virus in tears and recurrent corneal HSV can be induced following UV-B exposure of latently infected HLA Tg mice. Moreover, considering the wealth of data addressing the protective mechanisms of CD8 ϩ T cells specific to mouse HSV-1 epitopes (mostly the gB 498-505 epitope in B6 mice), it is surprising how few reports exist exploring the protective mechanisms of CD8 ϩ T cells specific to human HSV-1 epitopes (27,54,58,59). Our "humanized" HLA Tg mice express the human HLA-A*0201 molecule, instead of mouse H2 b major histocompatibility complex (MHC) molecules (4).…”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrated that both shedding of reactivated virus in tears and recurrent corneal HSV can be induced following UV-B exposure of latently infected HLA Tg mice. Moreover, considering the wealth of data addressing the protective mechanisms of CD8 ϩ T cells specific to mouse HSV-1 epitopes (mostly the gB 498-505 epitope in B6 mice), it is surprising how few reports exist exploring the protective mechanisms of CD8 ϩ T cells specific to human HSV-1 epitopes (27,54,58,59). Our "humanized" HLA Tg mice express the human HLA-A*0201 molecule, instead of mouse H2 b major histocompatibility complex (MHC) molecules (4).…”
Section: Discussionmentioning
confidence: 99%
“…“Tissue‐resident” memory T cells have downregulated S1PR1, like CD69 + bone marrow memory T cells 33. “Tissue‐resident” memory T cells, despite expressing CD69, rest in terms of proliferation and expression of effector molecules 160, 163. “Tissue‐resident” memory CD8 + T lymphocytes have a typical gene expression signature, and express the transcription factor Hobit 134, 159.…”
Section: “Tissue‐resident” Vs Bone Marrow‐resident Memory T Lymphocytesmentioning
confidence: 99%
“…Specifically, T RM cells offer superior functionality in settings of persisting infection, especially during periods of latency when inflammation and recruitment from the blood has been extinguished. Such dissociation from the recirculating memory pool is seen during latent HSV infection (85), which is also likely to feature Ag expression that is too low for the activation and recruitment of circulating T cells (86). In addition, this specialization probably extends to the final stages of cleared infection, when pathogen load has declined to otherwise undetectable levels (40,58).…”
Section: T Rm Cells Are Specialized For the Control Of Sequestered Pmentioning
confidence: 99%